THE IMPACT OF TRUST ON VENDOR MANAGED INVENTORY (VMI) PERFORMANCE (Journal of Technology and Operations Management, 2017)
Lack of trust among partners can lead to failure of VMI program. Since, many study emphasized that trust has significant roles in VMI program, companies that involved in VMI program must well understood the role trust on their performance. However, there is still lack of study on to what extend trust can influence VMI performance. Therefore, the aim of this paper is to examine the impact of trust towards VMI performance. Questionnaire was the main instrument for the study and it was gathered from 101 of suppliers in manufacturing companies. The findings show that trust contributes to service and cost performance of VMI program. Although, literature suggest that trust has significant impact on both cost reduction and service improvement in VMI program, this study shows that there is a limited effect on cost and service performance. This study recommends that trust should be enhanced through the sharing of demand information in order to increase benefits of VMI program.